Integrated care for optimizing the management of stroke and associated heart disease: a position paper of the European Society of Cardiology Council on Stroke. (11th May 2022) - Lip, Gregory Y H; Lane, Deirdre A; Lenarczyk, Radosław; Boriani, Giuseppe; Doehner, Wolfram; Benjamin, Laura A; Fisher, Marc; Lowe, Deborah; Sacco, Ralph L; Schnabel, Renate; Watkins, Caroline; Ntaios, George; et al.
Abstract: The management of patients with stroke is often multidisciplinary, involving various specialties and healthcare professionals. Given the common shared risk factors for stroke and cardiovascular disease, input may also be required from the cardiovascular teams, as well as patient caregivers and next-of-kin. Ultimately, the patient is central to all this, requiring a coordinated and uniform approach to the priorities of post-stroke management, which can be consistently implemented by different multidisciplinary healthcare professionals, as part of the patient 'journey' or 'patient pathway, ' supported by appropriate education and tele-medicine approaches. All these aspects would ultimately aid delivery of care and improve patient (and caregiver) engagement and empowerment. Given the need to address the multidisciplinary approach to holistic or integrated care of patients with heart disease and stroke, the European Society of Cardiology Council on Stroke convened a Task Force, with the remit to propose a consensus on Integrated care management for optimizing the management of stroke and associated heart disease. The present position paper summarizes the available evidence and proposes consensus statements that may help to define evidence gaps and simple practical approaches to assist in everyday clinical practice. A post-stroke ABC pathway is proposed, as a more holistic approach to integrated stroke care, would include three pillars of management: A: Appropriate Antithrombotic therapy. B: Better functional and psychological status. C: Cardiovascular risk factors and Comorbidity optimization (including lifestyle changes). Graphical Abstract: Graphical Abstract Integrated care for optimizing the management of stroke and associated heart disease: the post-stroke ABC pathway.